Expert ASP.NET Web API 2 for MVC Developers - Freeman, Adam (Apress : Imprint: Apress, 2014)
Web API 2 is the latest evolution of Microsoft's web services toolkit, which allows the creation of RESTful applications built on the ASP.NET platform. It provides a standards-based approach and a high-productivity development model that makes it easy to deliver services to a wide-range of clients, including mobile devices. This book puts Web API into context for the experienced MVC Framework developer and dives deep into the tools and techniques required to build Web API applications that integrate with the MVC Framework and shows you how to create single-page applications to consume them. Best-selling author Adam Freeman explains how to get the most from Web API 2 by building on the foundation of the MVC Framework and the ASP.NET platform. He starts with the nuts-and-bolts and shows you everything through to advanced features, going in-depth to give you the knowledge you need.